Aerobic program and work stress - Mamani-Quispe, Nelly-Edith; Mamani-Jilaja, Dometila; Casa-Coila, Manuela (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
This book is an adaptation of a research presented at the National University of the Altiplano - Peru, which aimed to determine the degree of incidence of the aerobic step program on work stress for administrative staff that corresponds to a quasi-experimental design with a single pre and posttest group. The study population was 24 administrative workers who work in the positions of deanery secretaries, department directors, study directors and research directors to whom the step aerobics program was applied. To measure work stress, the questionnaire by Prieto and Trucco (1995) was used, based on three dimensions: physiological and psychological symptoms and behavioral stressors, consisting of 48 questions. The instrument was adapted and validated through expert judgment, the Cronbach’s Alpha statistician found was 0.879, very close to 1, which indicates that the instrument has a high consistency. The study concluded, through the T Student statistical test, with a coefficient 4.03 less than the alpha value equal to 0.05, that there is significant evidence of pre and posttest, therefore, before the experiment, 25% are in normal stress, 34% mild, 31% moderate and 10% severe. After the intervention, the physiological and psychological symptoms decreased significantly, showing levels: 38% normal, 39% mild, 17% moderate and 6% severe. Demonstrating the effectiveness of the step aerobics program in work stress, its permanent practice will improve work activities and the overall health of the university worker.